Qualitative and quantitative research on preferences and perceptions regarding HIV post-exposure prophylaxis among young women, men, female sex workers, members of the LGBTQ + community and people who inject drugs in Kenya, Nigeria and Zimbabwe - El-Sahn, Moushira; Elliott, Rose; El-Sahn, Mona; Garcia-Gurtubay, Ignacio; Kong, Karen; Wood Santos, Trisha; Mulwa, Raphael; Muthoka, Elizabeth; Lucas, Jeff (Frontiers in Reproductive Health, 2025)
IntroductionThe World Health Organization (WHO) recently updated its guidelines for HIV post-exposure prophylaxis (PEP). These guidelines recommend community delivery and task-sharing for PEP administration and suggest enhanced adherence counseling for those who initiate PEP. This work provides insights into considerations for optimizing people's knowledge, demand for, use of and adherence to PEP through new channels. This mixed-method study examined five research questions concerning the perceptions and experiences of various groups regarding accessing and utilizing PEP and explored opinions on alternate delivery options to broaden access.MethodsThe total number of end-users interviewed for this study via qualitative and quantitative interview methodologies was 1,156. We spoke with a total of 236 end-users through qualitative Focus Groups (FGs) and in-depth interviews (IDIs) and surveyed 920 end-users with a questionnaire in Kenya, Nigeria and Zimbabwe, including members of key populations (Female Sex Workers, Members of the LGBTQ + Community, People Who Inject Drugs).ResultsPrompted awareness of PEP varied across the study countries (56.2% overall). Healthcare providers (doctors and nurses) were cited by end-user respondents as primary sources of information on HIV and PEP. PEP information evaluation revealed that condomless sex or condom malfunction were the emergency situations that resonated most with end-users. The majority (86.4%) cited a perceived likelihood to use PEP if exposed to HIV. A general hospital was deemed most acceptable for PEP access by end-users in all three countries (81.2%); clinical routes were perceived as preferable in terms of broadening access to PEP, with key reasons being convenience (68.2%), trustworthiness (56.5%) and knowledge (56.5%). End-users emphasized the need for consistent, correct, and supportive interaction points with healthcare providers to complete PEP treatment and follow-up.ConclusionsWHO's recent update to the PEP guidelines recommends community-based distribution and task-sharing of PEP. Uptake is dependent on confidentiality and privacy of services as well as on increasing awareness and knowledge of the PEP pathway. Provision of PEP by healthcare providers needs to incorporate multiple end-user touch/access-points with emotional support for greater adherence, and our study highlights the different preferences and access contexts among end-users for PEP.